Instructor's Manual for Griffin's Invitation to public speaking - Scholz, T. M. Linda (Thomson/Wadsworth, 2006)
Help your students understand the power and importance of public speaking in their lives and in greater society. INVITATION TO PUBLIC SPEAKING will help your students acquire the speaking skills they'll need to succeed in your classroom and in the real world. Grounded in the rhetorical tradition while offering a fresh perspective, this text engages students in the public dialogue, encourages civic engagement and shows them that they will use these skills beyond the classroom. Griffin also explains the reasons why certain things must be done and, most importantly, why students would want to speak publicly. Numerous pedagogical tools, speech-building exercises, thoughtful real-life examples, an invigorating art program, and an engaging voice will help your students easily comprehend the text's basic concepts, apply them in and out of the classroom, and understand the importance of public speaking in their lives